Allicin Attenuated Advanced Oxidation Protein Product-Induced Oxidative Stress and Mitochondrial Apoptosis in Human Nucleus Pulposus Cells. (16th December 2020) - Xiang, Qian; Cheng, Zhangrong; Wang, Juntan; Feng, Xiaobo; Hua, Wenbin; Luo, Rongjin; Wang, Bingjin; Liao, Zhiwei; Ma, Liang; Li, Gaocai; Lu, Saideng; Wang, Kun; et al.
Abstract : Intervertebral disc degeneration (IDD) is one of the most common chronic degenerative musculoskeletal disorders. Oxidative stress-induced apoptosis of the nucleus pulposus (NP) cells plays a key role during IDD progression. Advanced oxidation protein products (AOPP), novel biomarkers of oxidative stress, have been reported to function in various diseases due to their potential for disrupting the redox balance. The current study is aimed at investigating the function of AOPP in the oxidative stress-induced apoptosis of human NP cells and the alleviative effects of allicin during this process which was known for its antioxidant properties. AOPP were demonstrated to hamper the viability and proliferation of NP cells in a time- and concentration-dependent manner and cause cell apoptosis markedly. High levels of reactive oxygen species (ROS) and lipid peroxidation product malondialdehyde (MDA) were detected in NP cells after AOPP stimulation, which resulted in depolarized mitochondrial transmembrane potential (MTP). Correspondingly, higher levels of AOPP were discovered in the human degenerative intervertebral discs (IVD). It was also found that allicin could protect NP cells against AOPP-mediated oxidative stress and mitochondrial dysfunction via suppressing the p38-MAPK pathway. These results disclosed a significant role of AOPP in the oxidative stress-induced apoptosis of NP cells, which could be involved in the primary pathogenesis of IDD. It was also revealed that allicin could be a promising therapeutic approach against AOPP-mediated oxidative stress during IDD progression.